Optimising prostate cancer pathways: Improving post‐biopsy waiting times in a tertiary centre - Shayan Soroush; Sean Lim; Prachi Beniwal; Gavin Wei; Ying Lu; Kylie Yen‐Yi Lim; Kirsten Holden; Matt Harper; Scott Donnellan; Weranja Ranasinghe (BJUI Compass)
Abstract Objectives To evaluate the effectiveness of a streamlined Prostate Cancer Care Pathway (PCCP) in reducing post‐biopsy waiting times and improving patient satisfaction in a high‐volume tertiary centre. Patients and Methods Patients undergoing prostate biopsies were prospectively followed through PCCP for one year and were retrospectively compared to 150 patients who were treated at our centre either immediately prior to PCCP implementation (2022) or during Covid‐19 lockdowns (2020). Waiting times were compared using the Kruskal‐Wallis H‐test. Patient satisfaction was assessed using the modified PCa Questionnaire for Patients (PCQ‐P). Results A total of 398 patients were included. 248 patients went through PCCP, compared with 75 patients pre‐PCCP implementation (2022) and 75 patients during the 2020 pandemic. The median time from biopsy to results post‐PCCP was 15.0 days (IQR 13.0–19.0). This was significantly shorter than pre‐PCCP introduction of 21.0 days (17.0–28.0) and during 2020 lockdowns, 18.0 days (14.0–21.0, p < 0.001). A total of 131 patients (52.8%) requiring treatment under PCCP were streamlined for multidisciplinary discussion following imaging at a median time of 38.0 (29.8–42.0) days and seen at Urology or Radiation Oncology Consultant clinic for treatment discussion at a median of 38.0 days (31.0–49.0), compared to 63.0 days (45.0–84.0) pre‐PCCP (2022) and 52.0 days in 2020 (38.0–75.0, p < 0.001). A total of 176 PCCP patients (70.1%) participated in PCQ‐P with 93.2% of participants reporting satisfaction with waiting time durations (n = 176). Conclusion PCCP implementation reduced waiting times in all post‐biopsy care measures following significant Covid‐19 delays in PCa care delivery. Streamlining resources using similar pathways can reduce waiting times in cancer care and other conditions to alleviate anxiety during healthcare system strain.